1991
DOI: 10.1007/bf00190001
|View full text |Cite
|
Sign up to set email alerts
|

Brassica napus pollen development during generative cell and sperm cell formation

Abstract: Brassica napus pollen development during the formation of the generative cell and sperm cells is analysed with light and electron microscopy. The generative cell is formed as a small lenticular cell attached to the intine, as a result of the unequal first mitosis. After detaching itself from the intine, the generative cell becomes spherical, and its wall morphology changes. Simultaneously, the vegetative nucleus enlarges, becomes euchromatic and forms a large nucleolus. In addition, the cytoplasm of the vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
(12 reference statements)
1
9
0
Order By: Relevance
“…The cytoplasmic channels in the in tine layer which are present at the closed anther stage may be involved in the translocation of nutritive solutes from the tapetum/locular fluid to the developing pollen grain (Mascarenhas, 1975;Pacini et al, 1985;Murgia et al, 1991). The disappearance of these cytoplasmic channels during the terminal stage of pollen maturation may mark the blocking of gametophytic-sporophytic exchange and indicate the isolation of the pollen grain from its environment.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic channels in the in tine layer which are present at the closed anther stage may be involved in the translocation of nutritive solutes from the tapetum/locular fluid to the developing pollen grain (Mascarenhas, 1975;Pacini et al, 1985;Murgia et al, 1991). The disappearance of these cytoplasmic channels during the terminal stage of pollen maturation may mark the blocking of gametophytic-sporophytic exchange and indicate the isolation of the pollen grain from its environment.…”
Section: Discussionmentioning
confidence: 99%
“…21, Agriculture and Agri-Food Canada, Ottawa, Ontario K1A 0C6, Canada. microspore, while the plastids and very small vacuoles accumulate at the opposite pole (Fan et al 1988, Kott et al 1988, Murgia et al 1991, Telmer et al 1993. Changes have also been observed in the actin microfilament (MF) and microtubule (MT) cytoskeleton (Simmonds et al 1991(Simmonds et al , 1998Hause et al 1992;Gervais et al 1994;Simmonds 1994;Simmonds and Keller 1999).…”
Section: Introductionmentioning
confidence: 92%
“…We have found that MFs in the phragmoplast are amongst the most stable of actin structures in microspore and pollen development as they are preserved by a variety of preparative techniques (Gervais et al 1994). After the first pollen mitosis, the bicellular pollen grain consists of a small generative cell, which is devoid of plastids, and a large vegetative cell (Fan et al 1988, Kott et al 1988, Murgia et al 1991, Telmer et al 1992.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the elaioplast, another type of lipid body has been described in the tapetal cytoplasm of a wide range of plant families including the Liliaceae (Reznickova and Willemse 1980), Apocynaceae (Cousin 1979), Tiliaceae (Hesse 1993), Lamiaceae (Ubera Jimenez et al 1996, Geraniaceae (Weber 1996) and it is particularly well described in the Brassicaceae (Dickinson and Lewis 1973;Polowick and Sawhney 1990;Murgia et al 1991;Ferreira et al 1997;Wang et al 1997;Wu et al 1997;Murphy and Ross 1998). Similarly to cytoplasmic storage oil bodies from seeds (Hills et al 1993;Sarmiento et al 1997), the tapetal cytoplasmic lipid bodies are probably derived from the ER (Hesse 1993;Hesse and Hess 1993;Weber 1996;Murphy and Ross 1998).…”
Section: The Pollen Coatmentioning
confidence: 99%